Validating the autoregressive model of the Angat Reservoir monthly inflows - Dizon, Cornelio Q. (Philippine Engineering Journal)
Thirty six years of historical streamflow records (1946 to 1985), before and after construction of the Angat Reservoir, were used to identify the time series model that can forecast the Angat Reservoir monthly inflows. After more than twenty (20) years when the autoregressive model of the Angat Reservoir inflows was identified in a previous study by this author, its effectiveness and practicality to forecast the monthly inflows to the Angat Multipurpose Reservoir is validated by comparing the generated model outputs with recent observed measurements from 1986 to 2008. The paper presented the ARMA model selection process and showed the validity of the selected autoregressive model.